Fikih Bekerja - Fachri Fachrudin (JURNAL ALAMIAH, 2020)
Islam is not a religion that only has a vertical dimension between a servant and his Lord, it is a way of life that regulates all aspects of human life, including the relationship between a human being and another human being. Including Islam regulates how a human being maintains the existence of his life in the world. One of the main goals of Islam is hifdz al-mal, which is to protect property, which is the right of every human being. From here Islam gives freedom for humans to seek wealth as a tool to fulfill their lives. Islam gives a very high appreciation in work. The basic principle in Islam is to do a job that is valuable and useful, and vice versa, work that is useless and brings harm is declared as a forbidden job and even considered an ally of Satan. This can also be seen in the many verses of the Qur'an and Hadith that call on a Muslim to work.The verse of the Qur'an that regulates ethics in work is the word of Allah ta'ala in QS. Al-Anfaal: 27 "O you who believe, do not betray Allah and the Messenger (Muhammad) and (also) do not betray the mandates entrusted to you, while you know". In this verse it is stated that among the ethics that must be considered for people who work are being trustworthy and professional, namely carrying out the tasks that have been assigned to them with full responsibility. In addition, the hadiths of the Prophet which commanded to work in a lawful way and stay away from all forms of unlawful things are very numerous, including his words, "There are three signs of hypocrisy; when he speaks he lies, when he makes a promise he breaks it, and when he is given a message he betrays."